2017
DOI: 10.1017/jfm.2017.569
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of partial cavity formation, shedding and the influence of dissolved and injected non-condensable gas

Abstract: In the present study, the experimental set-up of Ganesh et al. (J. Fluid Mech., vol. 802, 2016, pp. 37–78) is used to examine the dynamics of a shedding cavity by examining the vapour production rate of the natural cavity and determining how minimal injection of non-condensable gas can substantially alter the vapour production rate, the resulting cavity flow and the cavity shedding process. The influence of the dissolved gas content on the shedding natural cavity flow is also examined. High-speed visual imagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 31 publications
1
27
0
Order By: Relevance
“…Spanwise averages of volume fractions are determined through measurement of the line-averaged attenuation (Beer-Lambert's law). The system used has been described and evaluated by Mäkiharju et al (2013), Ganesh et al (2016), Mäkiharju, Ganesh & Ceccio (2017 and Wu et al (2019). The frame rate of the imaging system is 1000 fps.…”
Section: Experimental Set-upmentioning
confidence: 99%
“…Spanwise averages of volume fractions are determined through measurement of the line-averaged attenuation (Beer-Lambert's law). The system used has been described and evaluated by Mäkiharju et al (2013), Ganesh et al (2016), Mäkiharju, Ganesh & Ceccio (2017 and Wu et al (2019). The frame rate of the imaging system is 1000 fps.…”
Section: Experimental Set-upmentioning
confidence: 99%
“…Presence of NCG can influence cavitating flows in various ways (Briancon-Marjollet et al 1990;Kawakami et al 2005;Orley et al 2015;Makiharju et al 2017;Vennig et al 2017;Brandao et al 2018;Trummler et al 2018). Influence of dissolved and injected NCG in partial cavitation over a wedge has been considered by Makiharju et al (2017). They found that injection of NCG into the cavity suppressed vapor formation altering the dynamics of condensation shock formation.…”
Section: Introductionmentioning
confidence: 99%
“…Presence of NCG can influence cavitating flows in various ways (Briancon-Marjollet, Franc & Michel 1990;Kawakami, Gin & Arndt 2005;Orley et al 2015;Makiharju, Ganesh & Ceccio 2017;Vennig et al 2017;Brandao, Bhatt & Mahesh 2018;. Influence of dissolved and injected NCG in partial cavitation over a wedge has been considered by Makiharju et al (2017).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, it was suggested that with a sufficient reduction in the cavitation number (giving rise to greater cavitation propensity), large-scale, periodic cloud shedding can be observed and associated with the formation and propagation of a shock within the high void-fraction bubbly mixture in the separated cavity flow [5,6,8,9]. Jahangir et al [6] established within a venturi nozzle that cloud break-off was produced by the presence of the re-entrant jet for a cavitation number Cn > 0.95 while, for Cn < 0.75, cloud shedding was driven by bubbly shock effects generated by the collapse of previously shed cavities.…”
Section: Introductionmentioning
confidence: 99%
“…This transitional regime was also demonstrated by Pelz et al [7] where a relationship was established between the ratio of the Reynolds (Re) and the cavitation numbers, and the occurrence of this transitional regime. In the work of Ganesh et al [5,9] with the use of high-speed imaging and time-resolved X-ray densitometry of cavitation over the apex of a wedge, the features of the observed condensation shocks were related to the average and dynamic pressure, and the void fraction. The transition to strongly shedding conditions was associated with a drop in the speed of sound in the bubbly mixture within the partial cavity.…”
Section: Introductionmentioning
confidence: 99%